Restriction of mitochondrial oxidation of glutamine or fatty acids enhances intracellular growth of Mycobacterium abscessus in macrophages - Ho Won Kim; Ji Won Lee; Hoe Sun Yoon; Hwan-Woo Park; Young Ik Lee; Sung Ki Lee; Jake Whang; Jong-Seok Kim (Virulence)
Mycobacterium abscessus (Mab), a nontuberculous mycobacterium, is increasing in prevalence worldwide and causes treatment-refractory pulmonary diseases. However, how Mab rewires macrophage energy metabolism to facilitate its survival is poorly understood. We compared the metabolic profiles of murine bone marrow-derived macrophages (BMDMs) infected with smooth (S)- and rough (R)-type Mab using extracellular flux technology. Mab infection shifted BMDMs towards a more energetic phenotype, marked by increased oxidative phosphorylation (OXPHOS) and glycolysis, with a significantly greater enhancement in OXPHOS. This metabolic adaptation was characterized by enhanced ATP production rates, particularly in cells infected with S-type Mab, highlighting OXPHOS as a key energy source. Notably, Mab infection also modulated mitochondrial substrate preferences, increasing fatty acid oxidation capabilities while revealing significant changes in glutamine dependency and flexibility. R-type Mab infections exhibited a marked decrease in glutamine reliance but enhanced metabolic flexibility and capacity. Furthermore, targeting metabolic pathways related to glutamine and fatty acid oxidation exacerbated Mab growth within macrophages, suggesting these pathways play a protective role against infection. These insights advance our understanding of Mab’s impact on host cell metabolism and propose a novel avenue for therapeutic intervention. By manipulating host mitochondrial metabolism, we identify a potential host-directed therapeutic strategy against Mab, offering a promising alternative to conventional treatments beleaguered by drug resistance. This study underscores the importance of exploring metabolic interventions to combat Mab infection, paving the way for innovative approaches in the fight against this formidable pathogen.